ANALISIS PENGARUH KUALITAS PRODUK, HARGA, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Konsumen Mie Nges-Nges Banyumanik Semarang) - Deasy Paramitha, Mariska; Khasanah, Imroatul (Diponegoro Journal of Management, 2015)
This research was made based on a decrease in sales of Mie nges-nges in the period 2013 to 2014. The decline in sales can be formulated how consumers behave in a purchase decision amid the many culinary options in the area of Banyumanik Semarang. This study aimed to examine the effect of product quality, price, and location towards the purchase decisions of the product of Mie nges-nges.This research used accidental sampling with sample of 100 people from the consumer population of Mie nges-nges. The analytical method that had been used is multiple linear regression. The results of the study found that the following regression equation:Y = 0321 0352 X1 + X2 + X3 0349This result indicates that all the independent variables tested are positive and significant impact on customer satisfaction through the F test and t test. The most influential variable is the variable price 0.352 and the variable that has the smallest influence is the product quality 0.321.